Literacy on Blockchain and Cryptography among University Students - Mulyanto Nugroho, Aris Heri Andriawan; Achmad Yanu Alif Fianto (SEMINAR NASIONAL KONSORSIUM UNTAG SE INDONESIA, 2024)
Blockchain and cryptography are rapidly transforming global industries, yet literacy in these fields remains uneven, particularly among students. This article explores the state of blockchain and cryptography literacy within educational contexts, highlighting gaps, effective pedagogical strategies, and barriers to widespread adoption. The findings indicate that student knowledge levels vary significantly, with secondary education showing minimal exposure, while higher education programs achieve better outcomes in specialized fields like computer science. Effective teaching methods, such as project-based learning (PBL) and gamification, have been instrumental in demystifying complex concepts. However, challenges persist, including a lack of trained educators, resource constraints, and ethical and environmental concerns surrounding blockchain technologies. Addressing these issues requires integrating ethics into curriculums, promoting environmentally friendly practices, and leveraging global partnerships to bridge socioeconomic divides. By implementing these strategies, education systems can equip students with the necessary skills to navigate and innovate within the digital economy responsibly. This article concludes with recommendations for future research and action to enhance blockchain and cryptography literacy globally